Pengaruh Metode Demonstrasi Menggunakan Media Nyata Terhadap Hasil Belajar Siswa Pada Pembelajaran IPA Kelas IV SD N 88 Palembang - Sella Falenti; M. Taheri Akhbar; Mega Prasrihamni (Departement of Mathematics Education, 2023)
The purpose of this study was conducted to determine the effect of the demonstration method using real media on the results of learning science in class V SDN 88 Palembang. The method used is this research research using experimental research methods (experimental research). In this study, researchers used a quasi-experimental design, namely the posttest only control design. The subjects in this study were class IV.1 and class IV.2 which totaled 54 students. Data collection is done by testing and documentation techniques. The data analysis technique uses test questions which are tested for validity and reliability. The results of the data analysis showed that the results of the hypothesis test showed that the t value was 2.942 > 1.675 t table and the significance value was <0.05 (0.005 <0.05). So it can be concluded that there is an influence of the demonstration method using real media on student learning outcomes in Class IV Science learning at SDN 88 Palembang.